Mopane worm use, livelihoods and environmental change in Limpopo Province, South Africa - Sekonya, James George (Department of Environmental and Geographical Science, 2017)
For centuries, nontimber forest products have been key aspects of household diets throughout the world. In southern Africa, mopane worms are widely harvested for household consumption and traded for income generation. This study investigated the contribution of mopane worm harvesting to rural livelihoods, and the effects of environmental change on mopane worm harvesting in rural households in order to understand how households attain sustainable livelihoods under different tenure types in rural areas in Limpopo Province, South Africa. Specific objectives were to determine the current significance and contribution of mopane worm harvesting and trading to rural livelihoods; to gauge the perceptions of harvesters and traders on forms of environmental change which have affected mopane worm availability and how consumption and trade patterns have changed in the last 20 years; to assess access and management of mopane resources under different tenure types; and, to explore mopane worm use in the context of the sustainable livelihoods framework. The research was conducted in the villages of Bokmakierie, Matiyani, Ha Gumbu, Masisi, Zwigodini, and Mphambo in Vhembe district and Nkomo village in Mopani district in the Limpopo Province, South Africa. Additional interviews were conducted with traders at markets in Thohoyandou, Makhado, Malamulele, Giyani and Elim in the Vhembe and Mopane districts, Limpopo Province. The study employed qualitative methods to collect data and included semi-structured household and key informant interviews. The respondents and key informants were identified through snowball sampling techniques. The significance of mopane worms in the study area is three-fold: it is an important source of food, it is a valuable trading commodity, and it is an intrinsic part of local cultural practices. The findings of this study indicated that the historical value placed on mopane worms as a food source and trading commodity has been passed down for generations. Trading was found to be important form of employment for rural people who have limited prospects of formal employment, and had the potential to generate higher income levels than wage labour in rural contexts. The decline in mopane tree density, vegetation change, lower-than-normal precipitation, and higher-than-normal temperatures were the leading forms of environmental change which have significantly affected mopane worm availability and outbreak events. Household consumption and trade patterns were altered as a result of the weather and climatic conditions shock arising from the El Niño phenomenon. Land tenure type was found to be the primary determinant of resource management and access regimes in the harvesting areas. Within the context of the sustainable livelihoods framework, the following findings were made. The limited availability of mopane worms presented a key constraint for the households and traders. The high availability of labour from family of the harvesters suggests human capital is strong. Furthermore, the strong social links and networks which resulted from family-level and community-wide participation strengthened the social capital opportunities. Physical and financial capital were found to have greatest threat to the attainment of sustainable livelihood. Households suffer poverty and are not easily able to access financial resources. This served as a hindrance for households and limited their income earning potential. In respect of these findings the following recommendations are made: further empirical investigations should be undertaken to determine the status of mopane worm populations; improved cooperation between traditional leaders, harvesters and local government is suggested as an option for management of the communal harvesting areas; the interplay between access, land tenure and harvesting requires further research.